2016
DOI: 10.1186/s12913-016-1699-5
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ perspectives, knowledge and skills regarding community case management of childhood diarrhoea and pneumonia: a qualitative inquiry for an implementation research project “Nigraan” in District Badin, Sindh, Pakistan

Abstract: Background: Pakistan's Lady Health Worker Programme aims to provide care to children sick with pneumonia and diarrhoea, which continues to cause 27 % under-five mortality in Pakistan. The quality of supervision received by Lady Health Workers (LHWs) in the programme influence their knowledge and skills, in turn impacting their ability to provide care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…When asked about services provided during the visit, caregivers most frequently reported polio vaccine administration (79% intervention arm [n = 3494] vs 78% comparison arm [n = 3531]) and vaccination (34% intervention arm [n = 3494] vs 32% comparison arm [n = 3531]). This finding corroborates LHWs’ statements in qualitative interviews that ‘we are best seen as polio workers’ . Less than 1% of caregivers in both arms (intervention n = 3494, comparison n = 3531) said that LHWs provide ORS, while less than 2% said that the LHWs provide any medicines.…”
Section: Resultssupporting
confidence: 79%
“…When asked about services provided during the visit, caregivers most frequently reported polio vaccine administration (79% intervention arm [n = 3494] vs 78% comparison arm [n = 3531]) and vaccination (34% intervention arm [n = 3494] vs 32% comparison arm [n = 3531]). This finding corroborates LHWs’ statements in qualitative interviews that ‘we are best seen as polio workers’ . Less than 1% of caregivers in both arms (intervention n = 3494, comparison n = 3531) said that LHWs provide ORS, while less than 2% said that the LHWs provide any medicines.…”
Section: Resultssupporting
confidence: 79%
“…A small number of studies used self-reported satisfaction, 64 motivation 58 or increased agency 57 as outcomes to measure the impact of ongoing training. These are what Kok et al 88 refer to as ‘software’ of a training programme and can affect motivation and performance.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Uganda shows that trust in CHWs and level of community awareness leads to higher utilization of CHW services [ 20 ]. In Badin, LHWs’ prestige in the community suffers due to lack of commodities and medicines [ 21 , 22 ]. CHWs’ respect and prestige is related to both CHWs’ own motivation and with community’s utilization of her services [ 14 , 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%